GABA and 5-HT Receptor Mediated Anxiolytic Effect of Essential Oil of Ferula sumbul Hook. Roots - Batra, Sonali; Kumar, Ashwani; Sharma, Anupam (Natural Products Journal, The, 2020)
Background: Ferula sumbul Hook. (Umbelliferae) roots have been traditionally used as sedative in nervous disorders. Objective: The present study identifies the components of essential oil of F. sumbul roots (EOFS) using GC-MS analysis and further evaluates mechanism-based anxiolytic potential of oil. Materials and Methods: EOFS was extracted using Clevenger apparatus, and was screened for anxiolytic activity using an elevated plus maze model. A battery of models was subsequently used to confirm the anxiolytic potential of EOFS. Further, benzodiazepine (BZD) receptor antagonist flumazenil and pentylenetetrazole (PTZ) were used for investigating the possible involvement of GABA receptors. Results: GC-MS analysis of EOFS revealed the presence of 32 components comprising triterpenoids and their derivatives. The oil exhibited significant anxiolytic activity at 50 μl/kg in various models like the elevated plus maze, light/dark, mirror chamber, open-field and mCPP-induced anxiety. The observation that anxiolytic effect of EOFS was completely blocked by benzodiazepine (BZD) receptor antagonist flumazenil, and partially by pentylenetetrazole, clearly demonstrates that anxiolytic activity of the oil is mediated mainly through BZD site on GABA receptors. Further, a significant reversal of mCPP induced anxiety by EOFS strongly indicates the possible involvement of 5-HT receptors in mediating anxiolytic activity of the oil. Conclusion: Results of the present study clearly demonstrates the anxiolytic potential of EOFS and, thus, validates the traditional relevance of the plant. This is the first report not only on multi-model based antianxiety activity of EOFS but also on the possible antianxiety mechanism of the oil.
Keywords: BZD